Gait Disorder in a Cohort of Patients With Mild and Moderate Alzheimer's Disease. (May 2016) - Castrillo, A.; Olmos, L. M. García; Rodríguez, F.; Duarte, J.
Gait disturbance results in an increase in the risk of falls in patients with Alzheimer's disease (AD). The falls are events that might be related to an increase in the number of fractures, loss of mobility, being bedridden, early institutionalization, and increased use of medication. Therefore, the reduction in the number of falls is important for the maintenance of the functional independence of the patients as well as for the prevention of sequelae resulting from those events. Alterations in the gait occur very frequently in AD, and the gait disturbance occurs relatively early in the course of the disease. This study has important implications for public health and clinical practice. This study and previous studies have reported that abnormal gait predicts greater risk of falls, dementia, institutionalization, and death. The high prevalence and incidence of abnormal gait and its association with multiple adverse outcomes in older adults require urgent attention. Our results allow us to identify the risk factors.